PENGARUH KOMUNIKASI PERSUASIF HOST LIVE SHOPPING TIKTOK SHOP AEROSTREET TERHADAP KEPUTUSAN PEMBELIAN FOLLOWERS - Andies Muhammad; Firdaus Yuni Dharta; Rastri Kusumaningrum (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
ABSTRACT This study attempts to ascertain the extent to which TikTok Shop live shopping host' persuasive communication affects followers' purchase choices. This sort of study employs basic linear regression analysis for data analysis and explanatory survey methods for quantitative research. There are 1,044,130 persons in total. This study used a non-probability sampling strategy with a simple random sampling method. The Slovin random sampling formula was used to determine the sample size, which consisted of 100 sample. The results of the data analysis show that there is an influence of persuasive communication by the Tiktok Shop live shopping host on followers' buying decisions with an F count of 50.885 with a significance level of 0.000 <0.05. From the results of the coefficient of determination, it is known that the persuasive communication of the Tiktok Shop live shopping host has an effect of 35.6% on purchasing decisions, while the rest is influenced by other variables not discussed in this study. Therefore, it can be said that the persuasion carried out by the live shopping host Tiktok Shop @Aerostreet was successful. Keywords: persuasive communication, live shopping, Tiktok Shop, purchasing decision.